Robotic Traffic Cone System for Lane Closure using Computer Vision and Decentralized PID Control - Saldaña, Angelo Casas; Campos, Manuel Martínez; Gutierrez, Daniela Zavala; Alegria, Elvis J. (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2024: Anais do XXI Simpósio Latino Americano de Robótica, 2024)
The manual placement of traffic cones increases the risk of accidents for road workers due to vehicle collisions. This paper proposes a system of cone-shaped robots that automatically position themselves to gradually close a lane. Image segmentation and Hough transform, with a neural networks model to correct position distortion, are proposed to estimate the position of each robot. Additionally, to implement decentralized PID control, the current position and orientation is determined by a Kalman filter in conjunction with an embedded gyroscope and the motor’s incremental encoders. Validation was conducted using three robots within a controlled, scaled-down environment.